2004
DOI: 10.1074/jbc.m312697200
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Augments K-Ras Activation and Triggers a Ras Signal That Attenuates ERK but Not Phosphoinositide 3-Kinase Activity

Abstract: Depending on the cellular context, Ras can activate characteristic effectors by mechanisms still poorly understood. Promotion by galectin-1 of Ras activation of Raf-1 but not of phosphoinositide 3-kinase (PI3-K) is one such mechanism. In this report, we describe a mechanism controlling selectivity of K-Ras4B (K-Ras), the most important Ras oncoprotein. We show that galectin-3 acts as a selective binding partner of activated K-Ras. Galectin-3 co-immunoprecipitated significantly better with KRas-GTP than with K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
275
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(305 citation statements)
references
References 52 publications
22
275
1
7
Order By: Relevance
“…[35] Galectin-3 functions in a similar way, but specifically for K-Ras. [36] These ancillary proteins are critical for the formation of nanoclusters: antagonizing Galectin-1 results in the displacement of H-Ras from the PM and in the inhibition of Ras biological activity. [37] Galectin-1 not only behaves as a key scaffold for the formation of H-Ras nanoclusters, it also functions as a molecular chaperone that contributes to H-Ras trafficking, by returning depalmitoylated H-Ras to the GC.…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
See 2 more Smart Citations
“…[35] Galectin-3 functions in a similar way, but specifically for K-Ras. [36] These ancillary proteins are critical for the formation of nanoclusters: antagonizing Galectin-1 results in the displacement of H-Ras from the PM and in the inhibition of Ras biological activity. [37] Galectin-1 not only behaves as a key scaffold for the formation of H-Ras nanoclusters, it also functions as a molecular chaperone that contributes to H-Ras trafficking, by returning depalmitoylated H-Ras to the GC.…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
“…[52] Effector usage can be influenced by site-specific regulatory proteins, as exemplified by Galectins: Galectin-1 diverts H-Ras signals to Raf-1 at the expense of PI3K, [38] whereas Galectin-3 attenuates ERK activation without affecting PI3K activity. [36] Ras trafficking can also impact on effector utilization. Ubiquitination of H-and N-Ras promotes their association to endosomes, where reduced availability of Raf results in diminished ERK activation.…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectin-1 and galectin-3 help stabilize H-RasGTP and K-RasGTP, respectively, when each isoform is localized in the correct lipid microdomain (discussed below) to promote high fidelity nanoclustering (13). The hydrophobic pocket of galectin is proposed to interact with the farnesyl group on Ras, potentially stabilizing the protein in the appropriate membrane orientation needed for a specific Ras-effector interaction (14). Although overexpression of galectins can increase Ras nanocluster output and has important implications in oncogenesis (13), proteins that bind the farnesyl group, such as phosphodiesterase-d and GDP dissociation inhibitors (GDI), can act as an "off-switch" for small GTPases by sequestering them from the membrane (15).…”
Section: C-terminal Posttranslational Modifications Govern the Ras-mementioning
confidence: 99%
“…It has been demonstrated that Galectin-3 favours a broad range of cancer cell activities, such as malignant cell transformation and tumour growth (62)(63)(64), cell adhesion, migration and invasion (65-69), anoikis resistance (70), apoptosis inhibition (71), (72) and angiogenesis (73).…”
Section: Protumourigenic Role Of Galectin3mentioning
confidence: 99%